ChemInform Abstract: A One‐Pot C—H Insertion/Olefination Sequence for the Formation of α‐Alkylidene‐γ‐butyrolactones. Issue 43 (21st October 2014) - Lloyd, Matthew G.; Taylor, Richard J. K.; Unsworth, William P.
Abstract The key C‐H insertion process of various diazo substrates is achieved in the presence of a dirhodium carboxylate catalyst.